Directors’ stock-purchases on stock performance: Evidence from Colombo Stock Exchange - D. D. C Kavinda; P. A. N. S Anuradha (International Journal of Financial, Accounting, and Management, 2022)
Purpose: This study examines how directors’ stock-purchase transactions would result in stock performance, assessing whether directors’ stock-purchase transactions are rapidly reflected in stock prices in Colombo Stock Exchange, Sri Lanka. Moreover, it studies how stock-purchase transactions based on directors’ gender, would result in stock performance. Research Methodology: The analysis covers a period from March 2013 to March 2019, and includes 141 directors’ stock purchases. Research issues are investigated using an event-study methodology. Results: Significant negative abnormal returns follow directors’ stock-purchase transactions, which indicates they are not rapidly reflected in stock prices. Gender-wise, male directors’ stock-purchase transactions result in significantly negative abnormal returns, whereas for its female counterpart, no significantly abnormal returns are observed. Further, both male and female directors’ stock-purchase transactions are not rapidly reflected in stock prices. Limitation: The study does not consider the number of shares purchased. Certain director stock purchases have to be omitted due to a lack of data. Contribution: Policy-makers could implement actions to prevent harmful trading activities and to improve the reporting timelines of directors' stock purchases. Consequently, the information asymmetry could be minimized. Hence, investors could engage in stock purchases confidently, which results in mitigating the company’s cost of capital.